Micro‐bacterial assessment of disposable gowns with a focus on green endoscopy in gastrointestinal endoscopy procedures: A Japanese pilot study for healthcare waste reduction - Sakiko Naito; Itaru Nakamura; Takahiro Muramatsu; Yasuyuki Kagawa; Masakatsu Fukuzawa; Takao Itoi (DEN Open)
Abstract Objective This study aimed to implement green endoscopy through the microbiological assessment of gowning techniques during endoscopy to reduce carbon emissions and separate medical waste. Methods Twenty‐five patients who performed esophagogastroduodenoscopy from March to May 2024 were included in this study. Four sections of the isolation gowns (anterior, posterior, right, and left) were cut into 2 cm2 after endoscopy, and the rate of microbial contamination was examined using the stamp method. Results The endoscopic examination time was 8 min (6−12), and endoscopy was performed by 10 expert endoscopists, six endoscopists, and nine residents. The overall isolation gown contamination rate was 56%, with 25%, 20.8%, 20.8%, and 33.3% in the front, back, as well as right and left arms, respectively. The rates of isolation gown contamination rates in the expert endoscopists, endoscopists, and residents groups were 30%, 50%, and 77.8%, respectively, with a higher rate in the residents group. Regardless of the physician's performance, bacterial detection was consistently higher in the left arm (42.9% vs. 40% vs. 25%; p = 0.093). The detected bacteria comprised 58% Gram‐positive and 42% Gram‐negative organisms, including those from tap water used for endoscopy bacteria and obtained from the participant's skin or mouth. No pathogenic organisms were detected. Conclusions The bacteria detected in disposable gowns after gastrointestinal endoscopy were non‐pathogenic. Thus, our findings suggest that changing all personal protective equipment of respective endoscopes might not be essential. We advocate for green endoscopy to achieve sustainable development goals and reduce medical waste.